ZO-1 Intracellular Localization Organizes Immune Response in Non-Small Cell Lung Cancer - Neyrinck-Leglantier, Déborah; Lesage, Julien; Blacher, Silvia; Bonnomet, Arnaud; Hunziker, Walter; Noël, Agnès; Dormoy, Valérian; Nawrocki-Raby, Béatrice; Gilles, Christine; Polette, Myriam (Frontiers in Cell and Developmental Biology, 2021)
Delocalization of zonula occludens-1 (ZO-1) from tight junctions plays a substantial role in epithelial cell plasticity observed during tumor progression. In vitro, we reported an impact of ZO-1 cyto-nuclear content in modulating the secretion of several pro-inflammatory chemokines. In vivo, we demonstrated that it promotes the recruitment of immune cells in mouse ear sponge assays. Examining lung cancers, we showed that a high density of CD8 cytotoxic T cells and Foxp3 immunosuppressive regulatory T cells in the tumor microenvironment correlated with a cyto-nuclear expression of ZO-1. Taken together, our results support that, by affecting tumor cell secretome, the cyto-nuclear ZO-1 pool may recruit immune cells, which could be permissive for tumor progression.